Plan estratégico para la empresa “Espinosa Aguirre servicios generales cía. Ltda.” De la ciudad de Loja, año 2016 - 2021. - Córdova Alvarado, María José (2016)
The aim of this thesis was to develop a strategic plan for the company "Espinosa Aguirre General Services CIA. LTDA "city of Loja, year 2016-2021 and to achieve this great goal the following specific objectives were defined: a) Develop a current diagnosis of the company Espinosa General Service Co. Aguirre. Ltda city of Loja to know its current market position and its environment; b) Conduct an external analysis to detect opportunities and threats that are affecting the activity of the company; c) Run an internal analysis to know their strengths and weaknesses on the market in which the company operates; d) Develop the SWOT and Matrix High Impact matrix; e) Ask strategic objectives; f) Implement an action plan and budget to meet the objectives. For this type scientific methodology was used through the methods: historical, mathematical, analytical and descriptive, deductive and inductive. The study began with the situational analysis of the company, where it was determined on the EFI 3,14 matrix, which allowed us to know that the company's strengths job security and customer loyalty; among its main weaknesses they are that it has not spread business philosophy and all staff are not motivated company. In the EFE matrix he was obtained 2.95 indicating that the company is taking advantage of the opportunities of the medium. Among the main opportunities identified are the possible increase in services in public and private enterprises and the use of biodegradable products; also its potential threats are low business growth in this city and the change of government in the next year. The high-impact matrix approach allowed five strategic objectives aimed at the administrative part of the company to eliminate the weaknesses and address threats repotenciando strengths and seizing opportunities. The budget for the implementation of the strategic plan requires an investment of $ 11,040.